2017
DOI: 10.18061/emr.v11i3-4.5300
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on: Solberg and Jensenius (2016) Investigation of 'intersubjectively embodied experience' in a controlled electronic dance music setting

Abstract: The motion capture study conducted by Solberg and Jensenius 2016 explores how people's movement on a dance floor is shaped by structural features of electronic dance music (EDM), with a particular focus on the breakdown and drop sections of tracks, the former being characterised by a reduction in musical texture and removal of the rhythmic bassline, and the latter when the rhythmic bassline re-enters and a thicker texture is re-established. The research also explored links between how the participants moved to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Further research should also seek to assess how and when strong emotional experiences are occurring on the dancefloor and whether these are related to musical aspects of EDM such as the break-routine, as suggested by Solberg (2014). Additionally, there is a need to assess the performative role of the DJ in live EDM event contexts, an integral factor of the musical experience which may influence physical and emotional responses of the audience (Gates et al, 2006; Greasley, 2017). Indeed, the current study found ‘DJ & performance’ to be an important sub-theme of the musical experience.…”
Section: Studymentioning
confidence: 99%
“…Further research should also seek to assess how and when strong emotional experiences are occurring on the dancefloor and whether these are related to musical aspects of EDM such as the break-routine, as suggested by Solberg (2014). Additionally, there is a need to assess the performative role of the DJ in live EDM event contexts, an integral factor of the musical experience which may influence physical and emotional responses of the audience (Gates et al, 2006; Greasley, 2017). Indeed, the current study found ‘DJ & performance’ to be an important sub-theme of the musical experience.…”
Section: Studymentioning
confidence: 99%